Panoramic Characterization of Spanish Spoken in Colombia:Phonology and Grammar - Bernal Chávez, Julio Alexander; Díaz Romero, Camilo Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article presents a panorama of some of the most general characteristics of Colombian Spanish, especially at phonological, morphological and syntactic levels. We begin with a contextualization of existing studies about Spanish in Colombia, along with a characterization of the average Colombian Spanish speaker. Secondly, following the diatopical division stated by Montes (1982), a reference to the linguistic peculiarities of each superdialect is made. Finally, we present the features of the Spanish spoken in areas that have contact with indigenous languages, and pending matters for further research regarding the different contact and diatopic varieties of Spanish in Colombia.